EFEKTIFITAS PROGRAM PELATIHAN KETERAMPILAN BAGI ANAK REMAJA PUTUS SEKOLAH DI UPT.PELAYANAN SOSIAL ANAK REMAJA TANJUNG MORAWA - FRISKA WINATI SIANTURI (Welfare StatE, 2013)
One of social problems that become a big challenge for Indonesian children, is a matter of neglect especially in relation to education. The issue has already taken root cause, and it is difficult to solve not only because the condition of the economy, but there are also caused by chaos in the family and factors influence the surrounding environmen. This research was meant to find out how the process and effectiveness program execution skill and guidance social teenagers drop out of school at PSAR Tanjung Morawa. Which is expected to give their own with the skill they have and restore  their social function. Type research used is descriptive which aims to give a sense or delineating exixsting reality of the society or group of people certain in field in the analysis that process is covering the decipherment the observation of one symptom observed or more, with population of as many as 150 people. In this case, the whole population of used as sample because if all, because the more the number of samples approaching the number of the population and the result of the research will representative to represent research or produce the result of research are getting better. The technique of collecting data obtained in research is through primary ( a questionnaire, data and endless hours ) and data secondary ( the study of literature ). Engineering data analysis used is a technique descriptive qualitative analysis where the data collected from a questionnaire and interview, a frequency distribution illustrated in the form of a diagram and then analysis. From the analysis result of that sanctions could be known that service program skill and guidance social given by PSAR Tanjung Morawa has been effective in prosper and make the child can stand alone by giving the  skills, Restore the social  function of child well, and training for independency residents. It can be seen because of a change or a positive development that is experienced by children binaan after they followed skill and guidance social services programs in PSAR Tanjung Morawa     Keywords : Effectiveness and Teen drop out of school